What are the most common running-related injuries? - empirical research based on anonymous surveys among people regularly involved in amateur long-distance runs - Monika Pająk; Kinga Grużewska-Piotrowska; Joanna Hubka; Agnieszka Grużewska; Wojciech Wcisło (Kazimierz Wielki University, 2023)
Introduction: The aim of the study: The aim of the study was to assess the most common injuries in people regularly involved in amateur long-distance runs by empirical research based on anonymous surveys. Materials and methods: The research material was collected using an anonymous online survey in May 2023. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: Of the 124 long-distance runners, 78,2% reported having a running-related injury in the past. The predominant site of these injuries was the lower limb especially foot, ankle and shin. 65,3% researched runners chose hard surfaces such as asphalt or pavestone. Conclusion: Definitely the highest number of injuries in our research is caused by an excessive training load. Most runners chose hard surfaces such as asphalt or pavestone which were not in line with the rules of injury prevention. Keywords: running, injury, running-related musculoskeletal injuries, sports injuries, rehabilitation.